2014
DOI: 10.4172/1948-5948.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genotyping of Escherichia coli and Pseudomonas aeruginosa Clinical Isolates for Oxacillinase Resistance and Mapping Susceptibility Behaviour

Abstract: In the present study, multi-drug resistant isolates of Escherichia coli and Pseudomonas aeruginosa were obtained from different clinical specimens and were subjected to molecular typing to detect the genes encoding oxacillinases in these isolates. Subsequently, antibacterial activity of drugs was tested against selected clinical isolates. Two hundred forty six isolates including 98 of E. coli and 148 of P. aeruginosa were collected from clinical specimens of different centers across India. Out of 246, 123 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…In this study, the concentration of sulbactam was higher than the conventional concentration, and this concentration may increase the affinity of sulbactam for class D β-lactamases and therefore the activity against these carbapenem-resistant A. baumannii isolates. Thus, we found that after adding a relatively high concentration of sulbactam with cefoperazone, the in vitro activity against carbapenem-resistant A. baumannii could be enhanced 15. However, further studies are warranted to elucidate the role of cefoperazone and sulbactam in the treatment of infection and assess β-lactamase gene expression.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the concentration of sulbactam was higher than the conventional concentration, and this concentration may increase the affinity of sulbactam for class D β-lactamases and therefore the activity against these carbapenem-resistant A. baumannii isolates. Thus, we found that after adding a relatively high concentration of sulbactam with cefoperazone, the in vitro activity against carbapenem-resistant A. baumannii could be enhanced 15. However, further studies are warranted to elucidate the role of cefoperazone and sulbactam in the treatment of infection and assess β-lactamase gene expression.…”
Section: Discussionmentioning
confidence: 92%
“…The study of Chaudhary and Payasi (19) showed a great diversity of occurrence of oxacillinase (OXA) genes among clinical isolates. OXA-48 and OXA-10 were more prevalent in both E. coli (32.6% OXA-48; 16.3% OXA-10) and P. aeruginosa (OXA-48 32.4%; 27.0%) as evident by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The attributed mechanisms to Enterobacteriaceae for resistance to carbapenems include the following: (i) efflux pumps, (ii) acquisition of β-lactamases encoding genes, such as carbapenemase; and (iii) modification of porins in the outer membrane and penicillin-binding proteins [ 4 ]. According to Ambler's molecular classification, beta-lactamases are grouped into four distinct classes, A (ESBLs), B (MBLs), C (AmpC), and D (OXA-types), based on their amino acid sequence [ 5 ]. The class D β-lactamases (oxacillinases) are a global crisis and significant concern due to being encoded by transmissible genes.…”
Section: Introductionmentioning
confidence: 99%